Proteomics-based analysis of the stress response of Bacillus cereus spores under ultrasound and electrolyzed water treatment - Zixuan Jia; Jianwei Zhou; Jingzeng Han; Donghong Liu; Ruiling Lv (Ultrasonics Sonochemistry, 2023)
Ultrasound is a green nonthermal technology with promising applications in microbial inactivation. Electrolyzed water has been investigated and found to have a synergistic inactivation effect of ultrasound on spores. This study used a data-independent-acquisition method to analyze the stress response of Bacillus cereus spores following ultrasound combined with electrolyzed water treatment. We identified 197 differentially expressed proteins under ultrasound combined with an electrolyzed water treatment for which the ratio in the metabolic pathway was the highest. Spores downregulated key proteins in energy metabolic and transportation pathways, in particular in phosphotransferase systems and ATP synthase under ultrasound, electrolyzed water, and combined stress. The results of this study revealed that the key proteins in intracellular metabolism decreased after ultrasound treatment, and the expression of small acid-soluble spore protein and cell wall biosynthesis protein increased. Meanwhile, DNA integration, recombination, and inversion protein and small acid-soluble spore protein were upregulated after electrolyzed water treatment. In general, the spores exhibited stress resistance under external stress. The inactivation of spores by further stress was reduced, which we called “cross-protection.”